[Person Walking at Askja] - Streng, Evelyn Fiedler (1975)
Photograph of a person walking at Askja. The person wears a blue jacket, brown pants, and an orange hat. They walk up black hill on a brown and red dirt path to the right. White water sits to the left, surrounded by the same dirt and black rock. Mountains covered in snow are visible in the background to the left.